A framework for evaluating EV battery mineral sourcing challenges - Nurcan Kilinc-Ata; Mahelet G. Fikru (Sustainable Futures)
The transition to electric vehicles (EVs) is pivotal for global decarbonization but faces significant challenges in securing essential battery minerals like lithium, graphite, manganese, cobalt, and nickel. While existing literature extensively explores individual challenges such as geographic concentration, geopolitical instability, and sustainability concerns, it often lacks a holistic framework to address their interconnected impacts on supply-demand dynamics. This report synthesizes insights from the extant literature to identify vulnerabilities in the mineral supply chain and proposes a strategic framework for sourcing policies. Key findings emphasize the need for developing mineral-specific sourcing policies, integrating sustainability criteria for mineral sourcing, and investing in technological innovations. These strategies could reduce transaction costs and mineral intensities while supporting the scaling of EV adoption.